The Role Of The Women Farmers Group In The Implementation of The "Pekarangan Pangan Lestari (P2L)" Program In Pancawati Village, Karawang Regency - Muchamad Raza Rifalah; Mohamad Sam'un; Fatimah Azzahra (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: This study aims to analyze the role of the Melati Women Farmers Group (KWT) in utilizing yards through the implementation of the Pekarangan Pangan Lestari Program (P2L) in Pancawati Village, Karawang Regency, and to assess the effectiveness of the program's implementation. Methodology: This study uses a descriptive quantitative method with data collection techniques through observation, interviews, documentation, and questionnaires. Data analysis techniques are used descriptively using a Likert scale instrument to measure roles (learning classes, collaboration vehicles, and production units) as well as an effectiveness approach based on indicators of program target accuracy aspects, program socialization and implementation aspects, program mentoring aspects, and program goal achievement aspects. Results: The results of the study indicate that the overall role of KWT Melati is categorized as very high with an average score of 88.35% in the aspects of learning classes, collaboration platforms, and production units. The implementation of the P2L Program is also classified as very effective with an average score of 114.75%, covering aspects of targeting accuracy, program socialization and implementation, program mentoring, and achievement of program objectives. Findings: The combined analysis of the role and effectiveness of the Sustainable Food Yard Program (P2L) simultaneously, with the use of official P2L indicators from the Directorate General of Horticulture. Novelty: Combining the analysis of the role and effectiveness of the Pekarangan Pangan Lestari Program (P2L) simultaneously, with the use of official P2L indicators from the Directorate General of Horticulture. Originality: This research offers a new perspective on the contribution of women farmers to household food security and rural economic empowerment through an evaluative approach based on measurable field data. Conclusion: The role of KWT Melati in the implementation of the P2L Program is classified as very high with an average score of 88.35%. The learning class and production unit aspects show active participation, while the cooperation aspect still needs to be improved. The program's effectiveness is also very effective with an average score of 114.75%, including targeting accuracy, socialization, mentoring, and goal achievement that successfully encourage group independence. Type of Paper: Quantitative Research.